Followership in British Christian churches: A comparative study - Krystin Zigan; YingFei G. Héliot; Alan Le Grys (Nonprofit Management and Leadership, 2024)
Emerging research on followership has overwhelmingly been focused on for-profit organizations. This research investigates four British congregations from different Christian denominations to explore how differing contexts shape the understanding of followership in nonprofit organizations. Using implicit followership theory, we analyze the value sets deriving from theological-ideological, institutional, and local contexts and explore informants' perceptions of ideal followership attributes. By conducting 26 semi-structured interviews with three different types of actors, we found that church members found themselves in a dialectic relationship between institutional norms and local settings, which shape the way followership is perceived. In terms of follower attributes, we identified faith-related and ethical as well as relational attributes to be prevalent. With this research, we advance current understandings of how effective leader-follower relationships in nonprofit organizations can be formed highlighting the importance of differing contexts for perceiving the role of followers.
Keywords: 650; Church organizations; contextual analysis; followership; implicit followership theory; volunteers